Impact of time spent in the trauma bay on mortality outcomes among level 1 trauma patients. (October 2019) - Adams, Logan; Tucker, Amber; Dennis, Jeff A.; Dissanaike, Sharmila
Introduction: The majority of trauma-related deaths occur within the first 24 h of injury, and time elapsed until intervention for an injury is one of the greatest causes of preventable death in mature trauma centers. This study seeks to determine if there is a correlation between time spent in the trauma bay and mortality outcomes. Methods: A retrospective analysis of Level 1 trauma patients from 1 January 2010 to 1 January 2016 in a single center. Results: Charts from 1678 Level 1 trauma patients with 1290 (76.9%) blunt and 388 (23.1%) penetrating injuries were analyzed. Of these, 345 patients died and 237 (68.7%) died within the first 24 h. Multivariate analysis yields an inverse correlation between increased times spent in the trauma bay and mortality, with controls for injury severity, age, and race/ethnicity and with deaths in the trauma bay excluded ( p < 0.001). Each additional minute spent in the trauma bay increases odds of surviving by 1%. However, increase in ISS and decrease in TRISS were directly correlated with reduced time in the trauma bay for both blunt and penetrating traumas. Results did not differ based on mechanism of injury or destination after the trauma bay. Conclusion: Reduced time spent in trauma bay was not correlated with improved mortality outcomes in Level 1 trauma patients. Findings do not necessarily suggest that increased trauma bay time would reduce mortality, but rather current evaluation procedures may prioritize trauma patients appropriately. Instinctive adjustment by emergency care providers to move more severely injured patients out of the trauma bay quicker and other additional variables could account for the measured phenomena. This is the first study to examine trauma bay times and mortality outcomes.